PENGARUH MANAJEMEN LABA AKRUAL dan RIIL TERHADAP KINERJA PERUSAHAAN DENGAN KUALITAS AUDIT SEBAGAI VARIABEL PEMODERASI - Perdana, Williyan Putra; Lasdi, Lodovicus (Jurnal Akuntansi Kontemporer, 2015)
Earning management is a strategy undertaken by management to correct the information in the financial statement, this strategy has a objective to maintain their interested parties. There are two strategies of earning management, the first is earning manage-ment through arbitrary undertaking items and earning management through real activities. After Sarbanes oxley act, manage-ment prefer to use earning management through real activities rather than earning management through arbitrary undertaking items. The purpose of this quantitative study is to test and analyze the effect of audit quality moderate the activity of the real earn-ings management through accruals and activity on firm performance. The object of research is the manufacturing companies listed on the Stock Exchange (Stock Exchange Indonesia) in 2009-2012. The samples used were 51 companies by using purposive sam-pling as a sampling technique and the technique of multiple linear regression analysis as a technique of data analysis. The results showed that the quality of Big 4 auditors affect the company's performance compared to non-Big 4 audit quality due in large KAP has a great resource. In this research audit quality moderates the real earnings management negatively affect the performance of the company so that no significant effect of audit quality, audit quality while moderating accrual earnings management negatively affect the performance of companies that audit quality had no significant effect. The mechanism of the company's operating cash flow composition, production, corporate expenses, discretionary accruals, audit quality, the size of the company.